Stunting Effect of Stimulation with Animation Video on the Development of Stunted Children - Ika Agustina Sulistyani; Yuni Kusmiyati; Sunartono Sunartono; Fatimah Sari (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2026)
Background: Stunting is a condition of failure to thrive in children under five as a result of chronic malnutrition so the child is too short for his age which has an impact on child development disorders. The right stimulation will stimulate the toddler's brain. Learning/stimulation media that combines text learning instructions with model illustrations or visualizations in the form of figures will be better than just containing words. This study aimed to determine the effect of animated video stimulation applications on the development of stunted toddlers Subjects and Method: This type of research is quantitative research with a quasi-experimental design. The sample size in this study was 30 people, 15 people in the animation video intervention group and 15 people in the standard method intervention group. The dependent variable was the development of stunted toddlers. The independent variable was animation video application. The data were collected by Functionality and Usability Questionnaire. Data analysis carried out in this research was univariate analysis and bivariate analysis using the paired t-test. Results: The video group showed an increase in the mean developmental score from 6.80 to 9.20 (Mean difference = 2.40), and this result was statistically significant (p= 0.007). The standard group also demonstrated an increase in the mean score from 7.80 to 8.47 (Mean difference = 0.60), and this result was statistically significant (p<0.001). However, the increase in the mean score was greater in the video group compared to the standard group, suggesting that animated video stimulation had a greater effect on the development of stunted children than the standard method. Conclusion: The application of animated video stimulation has an effect on the development of toddlers who experience stunting.